2022
DOI: 10.1021/acs.nanolett.2c02917
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Electrodynamic Behavior of Chlorophyll in a Plasmonic Nanocavity

Abstract: Plasmonic nanocavities have been used as a novel platform for studying strong light−matter coupling, opening access to quantum chemistry, material science, and enhanced sensing. However, the biomolecular study of cavity quantum electrodynamics (QED) is lacking. Here, we report the quantum electrodynamic behavior of chlorophyll-a in a plasmonic nanocavity. We construct an extreme plasmonic nanocavity using Au nanocages with various linker molecules and Au mirrors to obtain a strong coupling regime. Plasmon reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
1
1
0
Order By: Relevance
“…This is the most significant difference between the spectra compared to Fabry–Pérot nanocavity, which enhances the absorption of the individual components and broadens the absorption spectrum via shifting of the central absorption peak to the red and inducing a new absorption band to the blue of the LSPR peak. 34,35 Therefore, the observed enhancement is consistent with forming a Fabry–Pérot nanocavity, which broadens light absorption in some parts by as much as 20%. The observation is also consistent with Shi et al findings, 21 where they observed the most significant optical absorption when the nanocavity modes overlap with the Au NPs LSPR absorption.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…This is the most significant difference between the spectra compared to Fabry–Pérot nanocavity, which enhances the absorption of the individual components and broadens the absorption spectrum via shifting of the central absorption peak to the red and inducing a new absorption band to the blue of the LSPR peak. 34,35 Therefore, the observed enhancement is consistent with forming a Fabry–Pérot nanocavity, which broadens light absorption in some parts by as much as 20%. The observation is also consistent with Shi et al findings, 21 where they observed the most significant optical absorption when the nanocavity modes overlap with the Au NPs LSPR absorption.…”
supporting
confidence: 65%
“…[38][39][40][41] Kinetic traces extracted at the maximum of the winglets or minimum of the bleach provide information on plasmon excitation efficiency (delta absorption (DA) at time zero) and hot carriers' lifetime. The latter includes information about charge extraction from the plasmonic material in the presence of a suitable acceptor, 35,42 in the present case, CuSCN.…”
mentioning
confidence: 99%
“…[1][2][3] This exceptional ability provides a novel platform for access to biosensing, quantum chemistry and materials science. [4][5][6][7] In particular, plasmonic nanocavities have been demonstrated to exhibit promising applications in mediating chemical reactions. [8][9][10] In theory, vibrational energy relaxation (VER) is fundamentally important for chemical reaction dynamics owing to its intrinsic connection with energy dissipation at reaction active sites and chromophores, as well as its ability to govern reaction coordinates.…”
Section: Introductionmentioning
confidence: 99%